B, Analisis Bibliometrik Analisis Bibliometrik Pengaruh Skill Speaking Bahasa Inggris dalam Program Pertukaran Mahasiswa Internasional di Era Pandemi Covid-19: Analisis Bibliometrik Pengaruh Skill Speaking Bahasa Inggris dalam Program Pertukaran Mahasiswa Internasional di Era Pandemi Covid-19 - ROHMAH, NISWARISMA NAFISA (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
The article contains the results of research from researchers with the publication of the last five years of the journal, namely 2017 - 2021. The discussion shows how the influence of students who follow international student exchanges is related to English language skills both before and after the outbreak of the covid-19 pandemic.